1990
DOI: 10.1007/bf00016510
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol dehydrogenase gene expression in potato following elicitor and stress treatment

Abstract: A cDNA clone corresponding to a mRNA that rapidly accumulates during the hypersensitive-like response induced by elicitor treatment of potato (Solanum tuberosum L.) tuber was characterized. The clone encodes a polypeptide (Mr = 41,097) having 83%-85% amino acid identity with known plant alcohol dehydrogenase sequences (ADH; EC 1.1.1.1). The identity of the clone was confirmed by measuring the ADH enzyme activity in extracts of Escherichia coli transformed with the cDNA clone. In potato tuber disks, a wide rang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
33
0
1

Year Published

1990
1990
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(38 citation statements)
references
References 33 publications
(38 reference statements)
4
33
0
1
Order By: Relevance
“…Given that monoterpenol dehydrogenases are among the most highly expressed genes in secretory phase GTs (Lange et al, 2000;Ahkami et al, 2015), one may postulate that the ADH activity we observed is a nonspecific side activity of these enzymes. To test this hypotheses, we first performed a BLASTx search with the wellcharacterized ADH1 sequence from potato (Solanum tuberosum; Matton et al, 1990) against the peppermint GT transcriptome data set. This search indicated the presence of two putative orthologs (at roughly 88% identity for the translated peptide sequence) that were expressed at high levels in peppermint GTs (accession nos.…”
Section: Fermentation Is Active In Peppermint Gtsmentioning
confidence: 99%
See 1 more Smart Citation
“…Given that monoterpenol dehydrogenases are among the most highly expressed genes in secretory phase GTs (Lange et al, 2000;Ahkami et al, 2015), one may postulate that the ADH activity we observed is a nonspecific side activity of these enzymes. To test this hypotheses, we first performed a BLASTx search with the wellcharacterized ADH1 sequence from potato (Solanum tuberosum; Matton et al, 1990) against the peppermint GT transcriptome data set. This search indicated the presence of two putative orthologs (at roughly 88% identity for the translated peptide sequence) that were expressed at high levels in peppermint GTs (accession nos.…”
Section: Fermentation Is Active In Peppermint Gtsmentioning
confidence: 99%
“…The sequence of the well-characterized ADH1 from potato (Solanum tuberosum; P14673; Matton et al, 1990) was used to query our peppermint (Mentha 3 piperita) transcriptome assembly. Two contigs that contained genes with high identity (;88% at the peptide sequence level) and the corresponding cDNAs were amplified using Phusion DNA polymerase (New England Biolabs) with an annealing temperature of 60°C.…”
Section: Cloning and Characterization Of Adh From Peppermintmentioning
confidence: 99%
“…ADH activity is considered essential for the survival of plants during anaerobic conditions (66). Transcriptional activation of the Adh gene has also been noticed in response to several environmental stresses including saline conditions (67,68). In our experiment, ADH was induced under drought stress treatment.…”
Section: Discussionmentioning
confidence: 55%
“…침수 상태에서 합 성이 증가되는 단백질 중의 하나인 알코올 가수분해효소 (ADH: Alcohol dehydrogenase, EC 1.1.1.1)는 혐기적 조건 에서 식물이 적응하거나 생명을 유지하는데 필수적이며, 이 효소의 유전자 (Adh)의 전사는 침수 또는 산소 부족에 대한 특징적인 반응이 될 수 있다고 알려져 있다 (Sach et al, 1980;Johnson et al, 1994). 알코올 가수분해효소 활성도 변화는 토마토 (Genez et al, 1993), 아라비돕시스 (Chung and Ferl, 1999), 귀리 (Biemelt et al, 1998), 보리 (Mayne and Lea, 1984), 옥수수 (Andrew et al, 1994), 벼 (Ismail et al, 2009), 두과작물 (Fukuda et al, 2005), 감자 (Matton et al, 1990) (Sedbrook et al, 1996;Chung and Ferl, 1999;Peng et al, 2001). 식 물체가 생육하고 있는 상태에서 산소가 부족해지면 세포질 내 칼슘의 농도가 빠르게 증가하는 경향이 있으며 이러한 조건에서는 액포 등에 저장된 칼슘이 세포질로 유리되는 것 으로 추정하고 있다 (Subbaiah et al, 1998 (Subbaiah et al, 1994;Bush, 1996;Sedbrook et al, 1996).…”
unclassified